An interaction between SCTP and on demand MANET routing protocols - Azzali, Fazli; Mohd Zaini, Khuzairi; Osman, Baharudin; Abas, Azizi; Lubis, Fahrurrozi (2012)
Mobile Ad hoc Network (MANET) is a wireless network of mobile nodes that has no fixed routers.In MANET, mobile nodes can communicate via the wireless interface while nodes are moving freely without using the network infrastructure.Nowadays the performance of a new existence Internet protocol technology, that is Stream Control Transportation Protocol ( SCTP) in a MANET Routing Protocol still unknown.The general objective of this research is to analyze and make the comparative performance of SCTP with Ad-hoc On-demand Distance Vector (AODV) and Dynamic Source Routing protocol (DSR) using Network Simulator (NS-2).Specifically, this research is to measure the behavior of SCTP in terms of throughput and smoothness and; to determine routing protocol in Mobile Ad-hoc Network (MANET) either it has significant effect in SCTP.This research used Network Simulator 2 (NS-2), type of the traffic is Constant Bit Rate ( CBR) and packet size is 1000.The data sent consists of five speeds at 5 m/s, 10 m/s, 15 m/s, 20 m/s, 25 m/s, and then these speeds are used in AODV and DSR simulation.The result, of our study suggested that the SCTP throughput over AODV is higher than DSR and the smoothness of SCTP over DSR was higher than AODV for the five types of speed.In addition, there was no significant impact on throughput between AODV and DSR as the percentage difference was small (i.e., 0 to 2.4%).Furthermore, the speed of node movement does not significant affect the smoothness.